INTERNALISASI NILAI-NILAI RELIGIUS MELALUI INOVASI PEMBELAJARAN TAFSIR AMALY - Ragil Saefulloh; Ahmad Zahro (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Tafsir Amaly is who teaches the knowledge of the Qur'an from reading to how to practice it in everyday life. In addition, Amaly's Tafsir Learning has innovations in terms of strategies, approaches, models, and learning methods. So the purpose of this study is to understand how to internalize religious values to students through this Amaly Tafsir learning innovation. There are three problems examined in this thesis, namely: 1) How is the religious behavior of students, 2) How is Amaly's Tafsir learning innovation, 3) How is internalization of religious values students through the innovation of Amaly's Tafsir learning? The data collection technique in this research uses observation, interview, and document techniques. The technique data analysis used descriptive analysis techniques. In the process of checking the validity of the data in this study, several validity checking techniques used in the study were carried out, namely extending the research period, persistence of observation and triangulation. The results of this study indicate that the innovations of learning amaly's interpretation include: 1) Religious behavior of students, among others: ideological and ritualistic, namely the habit of praying in congregation, istighosah, sunnah prayers, obligatory fasting and sunnah; Consequential behavior is in the form of good deeds in longan gardens, in buildings, in rice fields and teaching the Koran in target schools, cooking pickets, cleaning pickets. Expressive behavior that is sincere in doing good deeds, tawadhu 'to teachers and kyai and UK, obeying the rules as well as critical and sharp in understanding the verses. 2) Amaly's Tafsir learning innovations include: lesson planning includes syllabus and lesson plans and so on; implementation of learning through innovative learning strategies and methods; learning evaluation includes the cognitive, affective and psychomotor values.3) Internalization of religious values through Amaly's Tafsir learning innovations include: moral knowing (knowledge of complete faith and Islam), exemplary (a pilot of the practice in the Tafsir Amaly material), moral action (ie invited to practice), moral loving/feeling (feelings experienced by students themselves when practicing), motivation (motivated to practice and teach) and habituation (Providing rules and obligations).